Polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystal and chain entanglement as well as preparation method and application of polyvinyl alcohol / polyethyleneimine conductive hydrogel

Through the cyclic freeze-thawing method and salting effect, a polyvinyl alcohol/polyethyleneimine conductive hydrogel based on crystallization and chain entanglement was prepared, which solved the problem of insufficient mechanical properties and stability of the hydrogel, achieved the controllability of performance and the convenience of large-scale mass production, and expanded its application prospects in various application fields.

CN119591905APending Publication Date: 2025-03-11NORTH CHINA ELECTRIC POWER UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411687894.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing hydrogel materials have shortcomings in mechanical properties and stability, which limit their application in flexible sensors and other fields. At the same time, their preparation process is complicated and costly, making it difficult to mass-produce on a large scale.

Method used

The hydrogen bond physical crosslinking grid between polyvinyl alcohol and polyethyleneimine was established by cyclic freeze-thawing method, and the mechanical properties and electrical conductivity of the hydrogel were quickly regulated through the salting effect, and conductive hydrogels based on crystallization and chain entanglement were prepared.

Benefits of technology

It significantly improves the mechanical properties and stability of the hydrogel, realizes the controllability of mechanical properties and conductivity, reduces the preparation cost, facilitates large-scale mass production, and expands its application prospects in the fields of health monitoring, array sensors and wearable devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591905A_ABST
    Figure CN119591905A_ABST
Patent Text Reader

Abstract

The invention discloses polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystal and chain entanglement as well as a preparation method and application of the polyvinyl alcohol / polyethyleneimine conductive hydrogel. Water molecules between polyvinyl alcohol and polyethyleneimine polymer chains are discharged through a circulating freezing-unfreezing method, a high-concentration accumulation area, namely a microcrystal area, in which the polymer chains are in close contact is formed, and rich physical entanglement and hydrogen bond interaction exist between the polyvinyl alcohol and the polyethyleneimine polymer chains. As a main physical crosslinking point, effective energy dissipation is provided, and the hydrogel is endowed with ultrahigh toughness. Besides, by utilizing the HofMichael effect, the inorganic salt solution generates a strong salting-out effect between polymer chains, reconstructs a local disordered structure and forms a stable physical cross-linked network, and compared with the traditional hydrogel, the preparation method is simple, convenient and easy to implement, low in cost and convenient for large-scale mass production. The prepared conductive hydrogel has controllable good mechanical properties and conductivity, and has wide application prospects in the fields of health monitoring, array sensors, wearable devices and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material science, and particularly relates to a preparation method and application of polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement. Background Art

[0002] Hydrogels have good biocompatibility, and water, ions, nutrients, and many other bio-related molecules can be freely transported through the pores of hydrogels. However, hydrogels have weak mechanical properties due to their high water content and loose cross-linking, and therefore cannot meet the needs of practical applications.

[0003] In recent years, the preparation of new hydrogels with high strength and toughness has become the focus of scientists to address the problems of low tensile strength and poor toughness of hydrogels. Salting-out effect treatment helps to prepare hydrogels with high mechanical strength, namely the Hofmeister effect, which refers to the fact that when hydrophilic ions are immersed in salt solutions, they reduce the solubility of proteins and other substances in water, thereby promoting their precipitation and aggregation in aqueous solutions. Generally, the ability of different anions to precipitate proteins is CO3 2- >SO4 2- >S2O3 2- >H2PO4 - >F - >CH3COO - >Cl - >Br - >NO3 - >I - >ClO4 - >SCN - .

[0004] In existing hydrogel technologies, common challenges include:

[0005] 1. The poor mechanical properties and insufficient stability of hydrogels limit their application in areas such as flexible sensors;

[0006] 2. Once the hydrogel material is formed, its mechanical and electrical properties cannot be adjusted, making its use scenario too limited;

[0007] 3. The preparation process of hydrogel is complicated, costly and difficult to mass produce. Summary of the invention

[0008] In view of the defects in the prior art, the purpose of the present invention is to provide a method for preparing polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement, which can simply and effectively regulate the mechanical properties and electrical conductivity of the hydrogel, establish a strong physical cross-linked grid formed by hydrogen bonds between polyvinyl alcohol and polyethyleneimine through a cyclic freeze-thaw method, and use the salting-out effect to quickly and controllably solve the problems of poor mechanical properties and insufficient stability of the hydrogel.

[0009] The first aspect of the embodiment of the present application provides a preparation method and application of polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement, comprising the following steps:

[0010] 1) First, a polyvinyl alcohol solution with a certain mass fraction is prepared and dissolved at high temperature, and then a polyethyleneimine with a certain molecular weight is added, and the mixture is heated and stirred to mix evenly;

[0011] 2) Secondly, the obtained mixed solution is added into a mold, and then placed in a refrigerator for a certain period of time and then fully thawed;

[0012] 3) Finally, the number of freeze-thaw cycles is controlled, and after thawing, the sample is placed in a salt solution with a certain mass fraction and fully immersed to obtain a polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement.

[0013] Furthermore, step 1) further includes: subjecting the mixed solution to ultrasonic treatment to remove bubbles.

[0014] Furthermore, the ultrasonication time is 5-10 min.

[0015] Furthermore, the ultrasonic time is preferably 8 minutes, which can not only ensure that the two polymer mixed solutions are evenly dispersed, but also eliminate bubbles and reduce the existence of stress defects.

[0016] Furthermore, in step 1), the high temperature is 80-95°C, the number average molecular weight of polyvinyl alcohol is 10,000-180,000, the degree of alcoholysis is 70%-99.9%, the mass fraction of polyvinyl alcohol aqueous solution is 10-30%, the molecular weight of polyethyleneimine is 1,000-20,000, and the heating and stirring temperature is 40-60°C.

[0017] Furthermore, in step 1), the high temperature is preferably 90° C., the mass fraction of polyvinyl alcohol is 10%, the molecular weight of polyethyleneimine is 10,000, and the heating and stirring temperature is 60° C. This condition can ensure that the two polymer chains are fully dissolved and gelled faster.

[0018] Furthermore, in step 2), the freezing temperature is minus 20-40°C, the thawing temperature is 25-40°C, the number of freeze-thaw cycles is 3-5 times, the mass fraction of the salt solution is 10%-saturated solution, and the thawing time is 8-24h.

[0019] Furthermore, the preferred freezing temperature is -20°C, the thawing temperature is 25°C, the number of freeze-thaw cycles is 3 times, the mass fraction of the salt solution is a saturated solution, and the thawing time is 8 hours. These conditions can ensure that the polyvinyl alcohol forms a regular crystalline structure and effectively improve the mechanical properties of the hydrogel.

[0020] Immersion in inorganic salt solution can produce a strong salting-out effect between the two polymer chains, promote the crystallization of polyvinyl alcohol and polyethyleneimine, thereby rebuilding the local disordered structure and rapidly improving the mechanical strength of the material.

[0021] Furthermore, in step 3), the type of salt selected is one or more of sodium carbonate, sodium sulfate, sodium acetate, sodium chloride, sodium nitrate, sodium iodide, calcium chloride, magnesium chloride, lithium chloride, potassium chloride, potassium acetate, and potassium nitrate.

[0022] The second aspect of the present invention also provides a polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement, which is prepared by the above method. The strength of the polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement is 6.44 MPa, the elongation at break is 689.2%, and the conductivity is 7.04 S / m.

[0023] The third aspect of the present invention also provides the use of the above-mentioned polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement in array sensors, health monitoring and electronic skin.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The hydrogel provided by the present invention, which is based on the physical crystallization region of polyvinyl alcohol and the chain entanglement structure formed by the polyethyleneimine polymer chain, can effectively improve the problems of the hydrogel being "brittle" or "soft".

[0026] (2) This patent uses a cyclic freeze-thaw method to expel water molecules between polyvinyl alcohol molecular chains, forming a high-concentration crystal aggregation area, namely the microcrystalline area, and provides effective energy dissipation, giving the hydrogel ultra-high toughness.

[0027] (3) This patent uses the Hofmeister effect to make inorganic salts produce a strong salting-out effect on polymer chains, rebuild the local disordered structure, and form a stable physical cross-linked network, thereby improving the mechanical properties and stability of the hydrogel. Combined with the salt washing-salt soaking process, the salt ions can be fully dispersed in the hydrogel network structure, which can effectively regulate the electrical properties of the material.

[0028] (4) The surface of polyethyleneimine in this patent contains a large number of amino groups, which are rich in positive charges in a nearly neutral solution, and can give the hydrogel excellent conductive properties. The preparation method is simple and easy, low-cost, and convenient for large-scale mass production. The prepared conductive hydrogel has good adjustable mechanical properties and conductivity, and has broad application prospects in the fields of health monitoring, array sensors, and wearable devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the schematic embodiments of the present application and their descriptions are used to explain the present application and do not constitute improper limitations on the present application.

[0030] Figure 1 The morphological changes of the hydrogels in Examples 1-6 before and after dehydration after being immersed in different salt solutions;

[0031] Figure 2 The stress-strain curves of the hydrogels in Examples 1-7 immersed in different salt solutions;

[0032] Figure 3 The bar graphs of the conductivity changes of the hydrogels in Examples 1-7 when immersed in different salt solutions;

[0033] Figure 4 The stress-strain curves of the hydrogels in Examples 3 and 11 immersed in different salt solutions;

[0034] Figure 5 The stress-strain curves and water content change diagrams of the hydrogel in Example 12 under different salt washing-salt soaking cycles. Figure a is the stress-strain curve after the first salt washing-salt soaking; Figure b is the stress-strain curve after the second salt washing-salt soaking; Figure c is the stress-strain curve after the third salt washing-salt soaking; Figure d is the water content under different times of salt washing-salt soaking cycles.

[0035] Figure 6 This is a curve diagram of relative resistance change of the hydrogel sensor prepared in Example 3 at different bending angles of the finger;

[0036] Figure 7The application of the hydrogel array sensor prepared in Example 3. Figure a is a hydrogel array sensor image without load; Figure b is an array sensor image when a finger presses a single site; Figure c is an array sensor image when a heavy object presses four sites; Figure d is an array sensor image when the pressing shape is "H" type; Figure e is an array sensor schematic diagram; Figure f is an array sensor image when the pressing shape is "O" type. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0038] Embodiment 1:

[0039] A 10wt% polyvinyl alcohol solution with a number average molecular weight of 80,000 was prepared at a high temperature of 80°C, followed by the addition of polyethyleneimine with a number average molecular weight of 1,600, and stirred at 40°C, mixed evenly, and ultrasonically defoamed; the resulting mixed solution was added to a mold, and then placed in a refrigerator for freezing at -20°C, freezing time for 12 hours, thawing at 25°C for 2 hours, and the number of freezing and thawing cycles was 3. After thawing, it was placed in a saturated sodium carbonate solution and soaked for 12 hours to obtain a polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement.

[0040] Embodiment 2:

[0041] A 10wt% polyvinyl alcohol solution with a number average molecular weight of 80,000 was prepared at a high temperature of 90°C, followed by the addition of polyethyleneimine with a number average molecular weight of 1,600, and stirred at 50°C, mixed evenly, and ultrasonically defoamed; the resulting mixed solution was added to a mold, and then placed in a refrigerator for freezing at -30°C, freezing time for 18 hours, thawing at 25°C for 4 hours, and the number of freezing and thawing cycles was 4. After thawing, it was placed in a saturated sodium sulfate solution for 18 hours to obtain a polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement.

[0042] Embodiment 3:

[0043] A 10wt% polyvinyl alcohol solution with a number average molecular weight of 80,000 was prepared at a high temperature of 95°C, followed by the addition of polyethyleneimine with a number average molecular weight of 1,600, and stirred at 60°C, mixed evenly, and ultrasonically defoamed; the resulting mixed solution was added to a mold, and then placed in a refrigerator for freezing at -40°C, freezing time for 24 hours, thawing at 25°C for 6 hours, and the number of freezing and thawing cycles was 5. After thawing, it was placed in a saturated sodium acetate solution for 24 hours to obtain a polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement.

[0044] The prepared hydrogel is connected to an electrochemical workstation and a computer to form a conductive path. The hydrogel is fixed on the tester's finger, and the relative resistance change at different bending angles is continuously monitored in real time. The electrical data is read by the computer. The hydrogel is assembled into an array sensor with 3 rows and 3 columns, and the 9 contact sites are connected to the computer port to form a pressure-responsive sensor, which is used to monitor the relative resistance change of objects such as fingers, heavy objects, "H" type, "O" type, etc. at different pressing sites.

[0045] Embodiment 4:

[0046] A 10wt% polyvinyl alcohol solution with a number average molecular weight of 80,000 was prepared at a high temperature of 90°C, followed by the addition of polyethyleneimine with a number average molecular weight of 1,600, and stirred at 50°C, mixed evenly, and ultrasonically defoamed; the resulting mixed solution was added to a mold, and then placed in a refrigerator for freezing at -30°C, freezing time for 36 hours, thawing at 30°C for 2 hours, and the number of freezing and thawing cycles was 3. After thawing, it was placed in a saturated sodium chloride solution for 24 hours to obtain a polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement.

[0047] Embodiment 5:

[0048] A 10wt% polyvinyl alcohol solution with a number average molecular weight of 80,000 was prepared at a high temperature of 90°C, followed by the addition of polyethyleneimine with a number average molecular weight of 1,600, and stirred at 60°C, mixed evenly, and ultrasonically defoamed; the resulting mixed solution was added to a mold, and then placed in a refrigerator for freezing at -40°C for 12 hours, thawed at 35°C for 3 hours, and the number of freezing and thawing cycles was 4. After thawing, it was placed in a saturated sodium nitrate solution and soaked for 12 hours to obtain a polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement.

[0049] Embodiment 6:

[0050] A polyvinyl alcohol solution with a number average molecular weight of 100,000 was prepared at a high temperature of 90°C, followed by the addition of polyethyleneimine with a number average molecular weight of 2,000, and stirred at 40°C, mixed evenly, and ultrasonically defoamed; the resulting mixed solution was added to a mold, and then placed in a refrigerator for freezing at -20°C, freezing time for 12 hours, thawing at 25°C for 2 hours, and the number of freezing and thawing cycles was 3. After thawing, it was placed in a saturated potassium chloride solution for 24 hours to obtain a polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement.

[0051] Embodiment 7:

[0052] A polyvinyl alcohol solution with a number average molecular weight of 120,000 was prepared at a high temperature of 90°C, followed by the addition of polyethyleneimine with a number average molecular weight of 4,000, and stirred at 50°C, mixed evenly, and ultrasonically defoamed; the resulting mixed solution was added to a mold, and then placed in a refrigerator for freezing at -30°C, freezing time for 18 hours, thawing at 25°C for 4 hours, and the number of freezing and thawing cycles was 4. After thawing, a polyvinyl alcohol / polyethyleneimine conductive hydrogel with only physical crystals was obtained.

[0053] Embodiment 8:

[0054] A polyvinyl alcohol solution with a number average molecular weight of 140,000 was prepared at a high temperature of 90°C, followed by the addition of polyethyleneimine with a number average molecular weight of 6,000, and stirred at 60°C, mixed evenly, and ultrasonically defoamed; the resulting mixed solution was added to a mold, and then placed in a refrigerator for freezing at -40°C, freezing time for 24 hours, thawing at 25°C for 6 hours, and the number of freezing and thawing cycles was 5. After thawing, it was placed in a saturated calcium chloride solution and soaked for 24 hours to obtain a polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement.

[0055] Embodiment 9:

[0056] A polyvinyl alcohol solution with a number average molecular weight of 160,000 was prepared at a high temperature of 90°C, followed by the addition of polyethyleneimine with a number average molecular weight of 8,000, and stirred at 40°C, mixed evenly, and ultrasonically defoamed; the resulting mixed solution was added to a mold, and then placed in a refrigerator for freezing at -20°C, freezing time for 36 hours, thawing at 25°C for 2 hours, and the number of freezing and thawing cycles was 3. After thawing, it was placed in a saturated magnesium chloride solution and soaked for 24 hours to obtain a polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement.

[0057] Embodiment 10:

[0058] A polyvinyl alcohol solution with a number average molecular weight of 80,000 was prepared at a high temperature of 90°C, followed by the addition of polyethyleneimine with a number average molecular weight of 1,000, and stirred at 50°C, mixed evenly, and ultrasonically defoamed; the resulting mixed solution was added to a mold, and then placed in a refrigerator for freezing at -30°C, freezing time for 48 hours, thawing at 25°C for 4 hours, and the number of freezing and thawing cycles was 4. After thawing, it was placed in a saturated lithium chloride solution and soaked for 24 hours to obtain a polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement.

[0059] Embodiment 11:

[0060] The polyvinyl alcohol solution with a number average molecular weight of 80,000 was mixed evenly at a high temperature of 90°C and ultrasonically defoamed; the obtained mixed solution was added to the mold and then placed in a refrigerator for freezing at a temperature of -40°C for 24 hours, thawed at 25°C for 6 hours, and the number of freezing and thawing cycles was 5. After thawing, it was immersed in a saturated sodium acetate solution for 24 hours to obtain a polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement.

[0061] Embodiment 12:

[0062] A polyvinyl alcohol solution with a number average molecular weight of 80,000 at a high temperature of 90°C is then added with polyethyleneimine with a number average molecular weight of 1,600, and stirred at 60°C, mixed evenly, and ultrasonically defoamed; the resulting mixed solution is added to the mold, and then placed in a refrigerator for freezing, the freezing temperature is -40°C, the freezing time is 24 hours, and thawed at 25°C for 6 hours, and the number of freezing cycles is 3. After thawing, it is placed in a saturated potassium acetate solution and soaked for 24 hours to obtain a polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement. It was tested using a universal tensile machine, then soaked in 2L of deionized water for 24 hours, the water was changed 5 times in the middle, and the universal tensile machine was used again for testing, and repeated 3 times. The performance and structural analysis of the hydrogels prepared in Examples 1-12 are as follows.

[0063] Figure 1 The morphological changes of the hydrogels prepared in Examples 1-6 before and after dehydration; the salting-out of anions conforms to the classic Hofmeister effect: CO3 2- >SO4 2- >S2O3 2- >H2PO4 - >F - >CH3COO - >Cl - >Br - >NO3 - >I - >ClO4 - >SCN - .

[0064] Figure 2 The stress-strain curves of the hydrogels in Examples 1-7 immersed in different salt solutions are shown in Figure 2. The hydrogels in Examples 1-7 were subjected to tensile tests using a universal material testing machine. Figure 2 It can be seen that the mechanical properties of the hydrogel can be changed by adjusting the type of ions, and based on this, the mechanical properties of the hydrogel can be controlled and optimized to achieve performance regulation, and the effect of anions is significantly greater than that of cations. In addition, the mechanical properties of the polyvinyl alcohol / polyethyleneimine conductive hydrogel can be further optimized by adjusting the concentration of the salt solution.

[0065] Figure 3 The following is a bar graph showing the conductivity changes of the hydrogels of Examples 1-7 when immersed in different salt solutions. The conductivity of the hydrogels of Examples 1-7 was compared using an electrochemical workstation. Figure 3 It can be seen that the polyvinyl alcohol / polyethyleneimine conductive hydrogel itself has conductive properties, which is due to the presence of mobile charges in the polyethyleneimine system. Figure 3 It can be seen that, generally speaking, the higher the mechanical properties of the hydrogel, the denser the network structure, which is not conducive to the transfer of charges, resulting in a decrease in conductivity.

[0066] Figure 4 The stress-strain curves of the hydrogels obtained in Examples 3 and 11 are shown in Figure 2. The hydrogels in Examples 3 and 11 were subjected to tensile tests using a universal material testing machine. Figure 4 It can be seen that after adding polyethyleneimine, the elongation at break increased from 390% to 730%, and the stress increased from 2.7 MPa to 3 MPa.

[0067] Figure 5 The stress-strain curves of the hydrogels prepared in Example 12 under different salt washing and salt soaking cycles are shown in Figure 12. The tensile tests of the hydrogels after each treatment in Example 12 were carried out by a universal material testing machine. Figure 5 It can be seen that as the number of cycles increases, the stress and strain of the hydrogel gradually increase, and remain unchanged after reaching 3 cycles, and the water content also remains unchanged.

[0068] Figure 6 The following is a curve diagram of the relative resistance change of the hydrogel sensor prepared in Example 3 at different bending angles of the finger. Figure 6 It can be seen that when the finger is bent at 30°, 45°, and 90°, the relative resistance change curve presents a step-like shape and has good cycle stability.

[0069] Figure 7 The application of the hydrogel array sensor prepared in Example 3. Figure 7It can be seen that single-point pressure, heavy object pressing, and pressure of heavy objects of different shapes on the 3 rows and 3 columns of the hydrogel array sensor have precise deformation responses and present different shapes, demonstrating good array sensing capabilities.

Claims

1. A method for preparing a polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement, characterized in that: The following steps are involved: 1) First, a polyvinyl alcohol solution with a certain mass fraction is prepared and dissolved at high temperature, and then a polyethyleneimine with a certain molecular weight is added, and the mixture is heated and stirred to mix evenly; 2) Secondly, the obtained mixed solution is added into a mold, and then placed in a refrigerator for a certain period of time and then fully thawed; 3) Finally, the number of freeze-thaw cycles is controlled, and after thawing, the sample is placed in a salt solution with a certain mass fraction and fully immersed to obtain a polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement.

2. The method for preparing polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement according to claim 1, characterized in that: The step 1) further comprises: subjecting the mixed solution to ultrasonic treatment to remove bubbles, wherein the ultrasonic treatment time is 5-10 minutes.

3. The method for preparing polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement according to claim 1, characterized in that: In step 1), the high temperature dissolution temperature is 80-95°C, the number average molecular weight of polyvinyl alcohol is 80,000-180,000, the alcoholysis degree is 70%-99.9%, the mass fraction of polyvinyl alcohol aqueous solution is 10-30%, the molecular weight of polyethyleneimine is 1,000-20,000, and the heating and stirring temperature is 40-60°C.

4. The method for preparing polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement according to claim 3, characterized in that: Step 1) also includes: the high temperature is 90°C, the mass fraction of polyvinyl alcohol is 10%, the molecular weight of polyethyleneimine is 1600, and the heating and stirring temperature is 60°C.

5. The method for preparing polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement according to claim 1, characterized in that: In step 2), the freezing temperature is -20-40°C, and the thawing temperature is 25-40°C.

6. The method for preparing polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement according to claim 5, characterized in that: Step 2) also includes a freezing temperature of -20°C and a thawing temperature of 25°C.

7. The method for preparing polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement according to claim 1, characterized in that: In step 3), the number of freeze-thaw cycles is 3-5 times, the mass fraction of the salt solution is 10%-saturated solution, and the thawing time is 2-8 hours.

8. The method for preparing polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement according to claim 7, characterized in that: Step 3) also includes: the number of cycles of freezing and thawing is 3 times, the mass fraction of the salt solution is a saturated solution, and the thawing time is 8 hours.

9. The method for preparing polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement according to claim 1, characterized in that: In step 3), the type of salt selected is one or more of sodium carbonate, sodium sulfate, sodium acetate, sodium chloride, sodium nitrate, sodium iodide, calcium chloride, magnesium chloride, lithium chloride, potassium chloride, potassium acetate, and potassium nitrate.

10. The method for preparing polyvinyl alcohol / polyethyleneimine conductive hydrogel based on crystallization and chain entanglement according to claim 1, characterized in that: The polyvinyl alcohol / polyethyleneimine conductive hydrogel according to any one of claims 1 to 9 or the polyvinyl alcohol / polyethyleneimine conductive hydrogel according to any one of claims 1 to 9 is used as a matrix or conductive material.

11. Application of any one of the polyvinyl alcohol / polyethyleneimine conductive hydrogels based on crystallization and chain entanglement according to claim 10 in array sensors, health monitoring and electronic skin.

Citation Information

Cited By

  • Polyester elastomer and preparation method thereof

    CN121181865A